Stúdium genetickej väzby medzi autozómovou dominantnou formou amyotrofie Charcot-Marie-Tooth a tromi genetickými markermi chromozómu c. 1 - Ferák, V; Kádasi, L; Hrubisko, M; Siváková, D; Véghová, E (Ceskoslovenska neurologie a neurochirurgie, 1989)
In a large pedigree with the autosomal dominant form of Charcot-Marie-Tooth neuropathy type I (CMT 1) segregating in four generations, genetic linkage was studied between this disease and three genetic markers from the centromere region of chromosome 1: Duffy blood group (Fy), salivary and pancreatic isoamylases (AMY 1, AMY 2), and DNA polymorphism at the antithrombin III locus, detected with the probe pAT3c. The lod-scores found do not support linkage between CMT 1 and both Fy and AT 3, since they are negative for all recombination frequencies. Very close linkage could have been excluded. For the AMY polymorphism, the pedigree was not linkage-informative. In agreement with the data from literature, these results support the notion of genetic heterogeneity of CMT 1: in the pedigree under study, the responsible locus is probably not in the centromeric region of the chromosome 1, where it was shown to map to in several other pedigrees. Thus, there seem to exist at least two loci responsible for this type of CMT disease.
Keywords: spinální svalová atrofie; isoamylasa; Genetic Linkage; antithrombin III; Pedigree; rodokmen; Charcotova-Marieova-Toothova nemoc; genetická vazba; Charcot-Marie-Tooth Disease; lidské chromozomy, pár 1; Humans; Isoamylase; Antithrombin III; dominantní geny; krevní skupiny - systém Duffy; Chromosomes, Human, Pair 1; Duffy Blood-Group System; Genes, Dominant; lidé; Muscular Atrophy, Spinal